Transcriptome profiling of intrahepatocytic Plasmodium and their host hepatocytes based on the infection phase and the zonation of the liver - Mo, Zhuning; Chen, Yuhong; Qin, Yujuan; Song, Jian (Frontiers in Genetics, 2025)
Intrahepatocytic development is a key stage in human Plasmodium infection, in which sporozoites replicate and transform into merozoites. Due to technological limitations, however, previous gene expression studies on malaria parasite liver infection were mostly conducted in vitro. In order to bridge these gaps, our current study compared the gene expression of in vitro-infected parasites at different time points with that of in vivo-infected parasites and revealed distinct patterns between parasite subpopulations in vitro and in vivo. A joint investigation of the Plasmodium transcriptome and their host transcriptome was carried out to confer a comprehensive analysis of gene expression in the liver stage of Plasmodium infection in vivo, which is similar to the disease setting, and therefore deepen our understanding of parasite and host transcriptional dynamics during intrahepatocytic infection.